HUMAN FACTOR IN THE IMPLEMENTATION OF THE STATE POLICY IN THE SPHERE OF INNOVATION ECONOMY DEVELOPMENT - Zhadan , O. (Theory and Practice of Public Administration, 2020)
The article is devoted to determining the peculiarities of the human factor influence on realization processes of the state policy in the sphere of innovative economy development in Ukraine and the world. The objective necessity of choosing an innovative model of economic development of Ukraine in the conditions of the national economic system integration into the systems of EU countries is substantiated. The legal and regulatory support of the formation and implementation of the state policy in the sphere of innovative economy development in Ukraine is generalized. The key changes in the system of social-labor relations, educational and scientific spheres are revealed due to the peculiarities of innovation activity, which determine the need for maximum and effective use of the creative potential of the workforce. Therefore, in order for the innovation economy to function effectively, the individual must act as a subject of economic relations, namely, the manufacturer of the innovative product and its consumer. In order to do this, it must not only possess creativity but also a desire for novelty, which is rooted in consciousness in both absolute value and risk (which is an indispensable condition for both production and consumption of innovation). In addition, the essential characteristics of an innovative personality include the readiness not only to respond positively to constant changes, but also to be the source of these changes. The task of forming a personality, which has the above characteristics, is formulated as a social order of modern society, implemented by public policy. However, this task can lead to contradictory consequences, because the perception of novelty as absolute value not only provokes the negativization of traditions, but also destroys the idea of ​​the stability of human being in the world.